2015
DOI: 10.1016/j.jallcom.2015.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrocatalytic performance of Co3O4/Ketjen-black cathodes for Li–O2 batteries

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The ESD technique can be applied to design suitable components and structures of catalysts. For example, a porous Co 3 O 4 /Ketjenblack cathode film was directly deposited on Ni foam by the ESD technique as the cathode of a Li–O 2 battery . The optimized Co 3 O 4 /Ketjenblack (80%) composite film exhibited the best performance.…”
Section: The Esd Technique For Li–o2 Batteriesmentioning
confidence: 99%
“…The ESD technique can be applied to design suitable components and structures of catalysts. For example, a porous Co 3 O 4 /Ketjenblack cathode film was directly deposited on Ni foam by the ESD technique as the cathode of a Li–O 2 battery . The optimized Co 3 O 4 /Ketjenblack (80%) composite film exhibited the best performance.…”
Section: The Esd Technique For Li–o2 Batteriesmentioning
confidence: 99%
“…In particular, SP's unique capability of generating hierarchical structures where key elements, such as sulfur active materials and oxygen evolution catalysts, are uniformly embedded in 3D porous frameworks can play a critical role in addressing the chronic issues of such emerging battery systems. [212][213][214][215][216][217][218] This article is protected by copyright. All rights reserved.…”
mentioning
confidence: 99%
“…Among these samples with different CoO x loadings (from 12.8 to 75.3 wt%), the 38.9 wt% CoO x /CG composite cathode showed the lowest average polarization of 1.17 V, but no more specific explanation was given. In contrast, a Co 3 O 4 /Ketjen black (KB) composite with different KB concentrations (from 20 to 80 wt%) was fabricated by Zhang et al 70 Benefiting from the compromise between electric conductivity and electrocatalytic activity, the Co 3 O 4 /KB (80 wt%) electrode exhibits the lowest overpotential less than 1.0 V and the most stable cycling performance. In addition, Wang et al 71 In addition to the material composition, the electrode microstructure was found to have a significant effect on the performance of oxygen electrodes in Li-O 2 batteries.…”
Section: Composite With Carbon Materialsmentioning
confidence: 99%